2021
DOI: 10.7759/cureus.19014
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Abusive Head Trauma Among Children in Saudi Arabia

Abstract: Background and objectives: To examine abusive head trauma (AHT) trends using data obtained from hospital-based child protection centers (CPCs) and the distribution of age in months among young children in Saudi Arabia.Methods: A retrospective study was conducted that includes data obtained from 58 hospital-based CPCs in all 13 regions of Saudi Arabia registered in the National Family Safety Registry from 2010 to 2020. AHT cases (n=106) were identified for inclusion in the registry by a daily review of the emer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…It is defined as "a devastating form of inflicted traumatic brain injury that occurs when a young child is and coma. Commonly mentioned risk factors for SBS are parents not expecting babies, single caregivers, parental depression, substance abuse, Low education and economic status (Alanazi et al, 2021;Mian et al, 2015). SBS carries a significant risk of serious complications most commonly, partial or total blindness, developmental delays, severe brain injuries and eventually death (Mian et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is defined as "a devastating form of inflicted traumatic brain injury that occurs when a young child is and coma. Commonly mentioned risk factors for SBS are parents not expecting babies, single caregivers, parental depression, substance abuse, Low education and economic status (Alanazi et al, 2021;Mian et al, 2015). SBS carries a significant risk of serious complications most commonly, partial or total blindness, developmental delays, severe brain injuries and eventually death (Mian et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…After this observation and considering the risks of SBS, parents' education should not be over looked. Since education and economic status are risk factors for SBS, increasing parents' awareness could reduce SBS incidence and complications (Alanazi et al, 2021). Furthermore, a pilot awareness program conducted in Saudi Arabia revealed that 77% of the participating parents had little to no knowledge of SBS risk factors, mechanisms and complications.…”
Section: Introductionmentioning
confidence: 99%